Teacher Professional Ethics and Codes of Conduct in Advancing Quality Education (SDG 4): A Comparative Study of Kenya and Indonesia. - Alwy Ahmed Mohamed; Triono Ali Mustofa; Mahmudul Hassan; Muhammad Rehan Sabir (Beginner: Journal of Teaching and Education Management, 2026)
This study looks at how teacher codes of conduct and professional ethics support high-quality education in Kenya and Indonesia that is in line with Sustainable Development Goal 4 (SDG 4). The study examines how institutional policies, cultural elements, and formal ethical frameworks affect teacher professionalism and student learning results in the two nations through a comparative analysis. According to the findings, Kenya uses a formal regulatory approach to improve accountability and discipline. The Teachers Service Commission enforces stringent codes of conduct that are backed by performance evaluation mechanisms. On the other hand, Indonesia places a strong emphasis on moral principles and professional ethics that are ingrained in educational institutions and social standards. Initiatives to help people internalise ethical behaviour include teacher training and fellowship programs. Despite their different enforcement strategies, both nations face issues such as uneven application, limited opportunities for professional growth, and cultural influences on moral behaviour. The study comes to the conclusion that enhancing teacher professionalism and promoting high-quality education in a variety of sociocultural contexts requires combining regulatory measures with continuing ethical education and leadership development.